Peningkatan Kualitas Produk UKM â€œPeyek Bunderâ€ Melalui Introduksi Teknologi Tepat Guna Spinner - Kusnandar Kusnandar; Mohd. Harisudin; Erlyna Wida Riptanti; Isti Khomah; Nuning Setyowati; Rr. Aulia Qonita (Jurnal Pengabdian UNDIKMA, 2023)
This community service activity aims to improve the quality of Peyek Bunder by introducing a spinner in the production process of small micro enterprises (SMEs) partnered with "Peyek Bunder". The method of implementing this community service includes socialization, introduction, and mentoring. Â The evaluation instrument of this activity uses the before and after comparison method and the evaluation is analyzed descriptively. The results of service activities in partner SMEs show that the quality of Peyek Bunder has increased. The oil content in Peyek Bunder has decreased, which can be seen from the condition at the bottom of the packaging that there is no oil seepage. This condition is due to a better draining process as it uses appropriate technology, namely the spinner. The draining process with a spinner takes about twenty minutes minutes for a capacity of 2 kilograms of Peyek Bunder. The results obtained are crisper and the durability is one month longer than without using a spinner.